Elimination diets – necessity or individual choice? - Rekowska, Martyna; Czerwionka-Szaflarska, Mieczysława (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Elimination diets are a standard of nutritional treatment in allergies, food intolerances, and congenital metabolic defects. The use of a long-lasting, restrictive elimination diet poses a risk of malnutrition and deficiencies of individual nutrients. In recent years, however, there has been an increase in their popularity among healthy people, including parents using various eliminations of food in their children. Incorrect nutrition, especially in infancy and early childhood, can have serious health consequences in subsequent life stages. A long-term elimination diet requires monitoring of its composition and the patient’s nutritional status, as well as assessment of their development and growth. Also, additional supplementation may be necessary.